Endoscopic Papillary Balloon Dilation for Removal of Choledocholithiasis: Indications, Advantages, Complications, and Long-Term Follow-Up Results - Chung, Joo Won; Chung, Jae Bock (Gut and liver, 2011)
Endoscopic papillary balloon dilation (EPBD) is an alternative method of endoscopic sphincterotomy (EST). Although concerns regarding post-procedure pancreatitis have been expressed, EPBD has come to be recognized as an effective and safe method for stone removal in specific cases. To analyze the proper indications, ideal methods, complications, and long-term follow-up results for EPBD, we reviewed articles about EPBD located through a search of the PubMed data base. We analyzed the ballooning methods, indications, results and complications of EPBD among the articles found and compared the results with those of EST. We considered the authors' own clinical experience and knowledge in developing recommendations for EPBD. EPBD showed similar efficacy and safety for the removal of choledocholithiasis to that of EST. Although large or multiple stones were difficult to remove by EPBD, it was safer and easier to apply in patients with coagulopathy or abnormal anatomy. To prevent severe pancreatitis, excessive ballooning and impractical cannulation should be avoided, and precut sphincterotomy or adjuvant prophylaxis should be considered. Due to its preservation of the sphincter of Oddi, EPBD is expected to have fewer long-term complications, such as stone recurrence, cholangitis and cholecystitis. In conclusion, EPBD appears to be safe and effective for the treatment of choledocholithiasis with proper selection of ballooning methods and patients.